OBM Geriatrics 2020
DOI: 10.21926/obm.geriatr.2004140
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Biomedical and Person-centered Care Approaches via Namaste Care with Family Participation: An Asian Experience in Advanced Dementia Treatment

Abstract: A locally-adapted, multisensory, psychosocial intervention called Namaste Care program was developed to improve the daily life of persons with advanced dementia (PwAD) through arranging meaningful activities and physical interactions by healthcare staff (Namaste Carers). Congruent with Asian values, the families of PwAD were invited to participate in Namaste Care sessions. The study aimed to explore the influence of Namaste Care on cognitive status and quality of life (QOL) of PwAD, and perceptions and attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…There seems to be an implicit understanding that caregivers will know the preferences and wishes of PWD though no prior discussions had occurred. Our findings concur with two local studies that highlight the influence of the family unit in the decision-making process [ 54 , 59 ], thus reinforcing the prominence of a collectivistic culture among Asians [ 60 , 61 ]. A family-centered ACP model, involving PWD and their caregivers, also has been reported to be suitable for Asian countries with a predominantly Chinese culture, where relational autonomy often times supersedes personal autonomy [ 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…There seems to be an implicit understanding that caregivers will know the preferences and wishes of PWD though no prior discussions had occurred. Our findings concur with two local studies that highlight the influence of the family unit in the decision-making process [ 54 , 59 ], thus reinforcing the prominence of a collectivistic culture among Asians [ 60 , 61 ]. A family-centered ACP model, involving PWD and their caregivers, also has been reported to be suitable for Asian countries with a predominantly Chinese culture, where relational autonomy often times supersedes personal autonomy [ 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies with the original Namaste Care have also shown a positive effect of the program on challenging behavior, 17 21 , 34 mood, 25 , 35 , 36 engagement, 22 , 25 , 34 , 36 interaction, 25 , 34 and quality of life. 25 , 37 , 38 The calm environment along with the undivided personal attention and meaningful activities may have contributed to this, as others have suggested. 39 , 40 Incidentally, NCF had a negative impact on residents, which was mostly due to them needing to get used to NCF or could be ascribed to a mismatch between the activity offered and the resident's preferences and needs.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies with the original Namaste Care have also shown a positive effect of the program on challenging behavior, [17][18][19][20][21]34 mood, 25,35,36 engagement, 22,25,34,36 interaction, 25,34 and quality of life. 25,37,38 The calm environment along with the undivided personal attention…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers in the present study perceived that the program helped them to incorporate structure and creativity in engaging in activities with persons with dementia, improved their understanding of meeting the needs of their family members, and brought them closer in their relationships through mutual enjoyment of activities. Other studies exploring the experiences of family caregivers in participating in delivering Namaste Care in LTC similarly found that they formed improved connections with persons with dementia through the program and preferred delivering activities in which they shared personal interests such as games [30,92].…”
Section: Discussionmentioning
confidence: 99%